Care seeking interval - an indirect measure of sexually transmitted infections related stigma: a prospective observational study - Sikkanthar, Syed Iqbal; Stephen, Anitha Christy; Shanmugasundaram, Sakthivadivu; A., Kayalvizhi V. (International Journal of Research in Dermatology, 2020)
Background: Stigma about STDs (sexually transmitted diseases) may influence an individual’s decision to disclose information about his/her sexual behaviour to health care practitioners as well as to their sex partners. This leads to a continued transmission of sexually transmitted infections (STI) and greater probability of adverse sequelae. Thus, care seeking interval may be regarded as an indirect measure of stigma associated with STI. The aim of this study is to assess healthcare-seeking behaviour of patients and the factors associated with its delay. Methods: This was a cross-sectional study conducted over a period of 1 year in STD OP of Government Stanley medical college, Chennai which included all symptomatic STD Patients who came to OP. The data were collected using a semi-structured questionnaire. The statistical package SPSS (version 16) was used for analysis. Results: The study included 492 males and 517 females who presented with STD related symptoms. Nearly 54% of patients sought care after 7 days of onset of symptoms. In that 52% of patients reported their delay to be due to fear of disclosure about their symptoms, 19% had self treatment, 12% of them expected spontaneous resolution, 8% had lack of awareness about their symptoms and the remaining 9% reported various other causes. Conclusions: Fear of stigmatisation has a positive association with increased care seeking interval in STDs. Addressing concerns about stigma and educating the public about timely heath care could help reduce the complications of STDs among high risk adult population thereby improving the quality of patient’s life.